Prevalensi Schistosomiasis pada Hewan Reservoir Sapi (Bos, sp) dan Kerbau (Bubalus, sp) dalam Sistem Peternakan Ekstensif di Lembah Napu, Sulawesi Tengah: Prevalence of Schistosomiasis in Reservoir Animals Cattle (Bos, sp) and Buffalo (Bubalus, sp) in Extensive Livestock System in Napu Valley, Central Sulawesi - Sagaf, Sagaf; Indang, Nur; Sigit, Sigit; Fahri, Fahri; Pribudi, Rully Akbar (Fakultas Peternakan Universitas Jambi, 2025)
Background: Schistosomiasis is endemic in Central Sulawesi, namely in Lindu, Bada, and Napu Valley. In the Napu Valley, schistosomiasis not only attacks humans but also mammals such as cattle and buffalo. Purpose: The aim of this research was to determine the prevalence of schistosomiasis in cattle (Bos sp) and buffalo (Bubalus sp.) in extensive livestock systems in the Napu Valley, Central Sulawesi. Methods: Sampling of cow and buffalo feces. Next, a stool examination was carried out to see the type of worm eggs microscopically using the Kato-Katz method at the Schistosomiasis Laboratory of the North Lore Health Service, Poso Regency. The number of samples used was 10 each, consisting of female cows, male cows, female calf cows, and male calf cows, as well as female buffaloes, male buffaloes, female calf buffaloes, and male calf buffaloes. Results: The research results found more than 1 species of worm eggs that infect cattle and buffalo, namely Schistosoma japonicum, Ascaris lumbricoides, Trichuris trichiura, and hookworm. The prevalence of schistosomiasis is higher in cows compared to buffalo; this is because cows have more attack power with more pores, so cows are more easily infected by parasites. Apart from that, cows also roam further in search of food than buffalo. When it rains, most buffalo just lie in a wallow. Unlike cows, even though it rains, cows still walk to look for food. Conclusion: The conclusion is that the prevalence of schistosomiasis is more common in cattle, namely 11 positive cases, and in buffalo there are only 2 positive cases.